USA Endometrial Cancer Projections to 2030: should we be concerned?. (December 2014) - Sheikh, M Aamir; Althouse, Andrew D; Freese, Kyle E; Soisson, Sean; Edwards, Robert P; Welburn, Sharon; Sukumvanich, Paniti; Comerci, John; Kelley, Joseph; LaPorte, Ronald E; Linkov, Faina
ABSTRACT : Aim: As the incidence of endometrial cancer (EC) increased considerably since 2007, this study aimed to project the burden of EC to the year 2030.Methods: Multivariate linear regression was used to project EC incidence by modeling trends in EC incidence from 1990 to 2013, while accounting for temporal changes in obesity, hysterectomy and smoking.Results: The best-fitting model predicting EC rates included a time effect plus effects for hysterectomy (12-year lag), severe obesity (3-year lag) and smoking (9-year lag). The best-fitting model projected an increase to 42.13 EC cases per 100, 000 by the year 2030, a 55% increase over 2010 EC rates.Conclusion: The projected increase of EC over next 16 years indicates the need for close monitoring of EC trends.